2020
DOI: 10.1038/s41541-020-00228-w
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical optimization of an enterotoxigenic Escherichia coli adjuvanted subunit vaccine using response surface design of experiments

Abstract: Enterotoxigenic E. coli (ETEC) is a leading cause of moderate-to-severe diarrhoea. ETEC colonizes the intestine through fimbrial tip adhesin colonization factors and produces heat-stable and/or heat-labile (LT) toxins, stimulating fluid and electrolyte release leading to watery diarrhoea. We reported that a vaccine containing recombinant colonization factor antigen (CfaEB) targeting fimbrial tip adhesin of the colonization factor antigen I (CFA/I) and an attenuated LT toxoid (dmLT) elicited mucosal and systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…According to the quality by design (QbD) framework, to obtain a robust adenovirus production process, a robust setpoint and design space for the process parameters should be explored using the design of experiment (DoE) approach (Zhang and Mao 2017 ). This strategy is available for antibodies and virus vaccines (Patel et al 2018 ; Poncet et al 2020 ) but has seldom been reported for adenovirus production.…”
Section: Introductionmentioning
confidence: 99%
“…According to the quality by design (QbD) framework, to obtain a robust adenovirus production process, a robust setpoint and design space for the process parameters should be explored using the design of experiment (DoE) approach (Zhang and Mao 2017 ). This strategy is available for antibodies and virus vaccines (Patel et al 2018 ; Poncet et al 2020 ) but has seldom been reported for adenovirus production.…”
Section: Introductionmentioning
confidence: 99%
“…Two separate immunogenicity experiments were conducted based on DOE and/or desirability index methodology adapted from a previous report (3). The first immunogenicity experiment focused on optimization of vaccine formulation component doses (LecA antigen, GLA, 3M-052, phospholipid) using a central composite DOE.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the association of stool IgA and PBMC IFNg with protection from amebiasis in humans informed the weighting factors of the immunological readouts employed in the DOE and desirability index analysis here. Even when correlates of immunity are known, the weighting of the various readouts will always have some degree of subjectivity and may require refinement as more knowledge is gained (3). Another potential benefit of the DOE and desirability index approach is identification of candidates that elicit different immune response profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tip adhesin complex was subsequently tested for immunogenicity when delivered transcutaneously with mutant LT (R192G) via patch in human volunteers (87). Although these studies indicate that additional effort will be required for optimal delivery of the fimbrial tip adhesin complex (121), recent studies of dscCfaE genetically fused in a chimeric complex with the A2 subunit of cholera toxin and the B subunit of LT (dscCfaE-sCTA2/LTB) resulted in substantial protection in an Aotus nancymaae model of infection, following intradermal vaccination with mLT(R192G) (89). Similar preclinical studies of CS6, an antigen present in~1/5 of ETEC strains have been ongoing.…”
Section: Development Of Cf and Cs Subunit Vaccinesmentioning
confidence: 99%